BAHASA PANTUN DALAM MAKNA DAN BUDAYA MASYARAKAT MELAYU BANGKA: SEBUAH KAJIAN ETNOLINGUISTIK - Dini Wulansari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
“Pantun Melayu Bangka” is one of the cultural heritages of Bangka Island and has become a unique identity for its people. This descriptive-qualitative study aims to describe and to explore the “pantun” as a picture of the Island’s condition. Data were analyzed by ethnolinguistics approach and supported by socio-cultural values in the form of linguistics characteristic and life reflected in the words, signs, or symbols. Therefore, ethnolinguistics plays an important role in this study not only in determining and relating the use of language and the meaning of “Pantun” itself but also in understanding the cultures. “Pantun” yields an interesting and effective way to make a person think and interprete any ideas logically and artistically as well with the proper diction and harmonization.